A collection of Islamic advertising principles - Shafiq, Ali; Haque, A. K. M. Ahasanul; Abdullah, Kalthom (Faculty of Economics and Management, Universiti Kebangsaan Malaysia (UKM), 2016)
Since long advertising is fraught with ill-practices of various nature and intensities. It has been criticized by Muslim and non-Muslim scholars alike, making it imperative to call for more ethical advertising. While ethics are usually relative and without an overarching watching body, it lacks uniform interpretation as well as enforcement. Islamic advertising is proposed as a potential solution to the unethical advertising practices. This conceptual paper, written after library research, gathers principles of Islamic advertising from the available literature, given by various religious and academic scholars. It was found that these principles satisfactorily provide a response to the criticism on advertising, at least in theory. It can be postulated that if these principles are applied most of the problems in, and related to contemporary advertisements can be curtailed.